Optimal design of eddy current damper in air bearing guided motion system - Sung, Eunho; Seo, Chang Hoon; Jeon, Yongho; Choi, Young Man; Kim, Kihyun; Lee, Moon G. (European Society for Precision Engineering and Nanotechnology, Conference Proceedings - 18th International Conference and Exhibition, EUSPEN 2018, 2018)
Performance of electronic devices has been improved with more precise manufacturing process. Semiconductor is typical electronic component that requires the high precision. In-position stability is one of important factors for the high-end manufacturing. To meet this demand, air bearings and linear motors are often used for the manufacturing equipment as a positioning mechanism. The air bearing forms an air film between the guide surfaces, and there is little friction. The use of air bearings is advantageous for the precise positioning because of the low friction, but the in-position stability is insufficient due to its low stiffness. Additional damping is needed to improve the in-position stability of air bearing guided motion system. When there is magnetic field change, eddy current in a conductor is generated and then a force opposite to and proportional to magnet's speed is produced like a damping component. This can give a damping force to the linear motion system and it takes advantage of the air bearing because it works without contact. Therefore, the Eddy current damping (ECD) makes the air bearing guided motion system more precise. In this paper, three novel designs of ECD module are proposed for the linear motion system with air-bearing and linear motor. The ECDs have Halbach magnet array as a magnetic field sources because the array confines the magnetic flux to the conductor. Experimental results present the improvement of the in-position stability. And then the advantages and disadvantages of each modules are described.
Keywords: Air bearing; Eddy current damper; Linear motion systems; Magnetic field sources; Manufacturing equipment; Manufacturing process; Motion system; Position stability; Air bearing; Eddy current damper; In-position stability; Motion system